Multi-UAV cooperative channel model for emergency communication - Lu BAI; Mingran SUN; Ziwei HUANG; Tao FENG; Xiang CHENG (Tongxin xuebao)
To carry out the system design and technology development for emergency communications, and greatly improve our ability of risk prevention and emergency disposal, the research on multi-unmanned aerial vehicle (multi-UAV) cooperative channel model for emergency communications was carried out.First, the channel dataset of multi-UAV cooperative emergency communications in two typical emergency environments, i.e., the urban earthquake and suburban blizzard, was established.The channel parameters and statistical properties of multi-UAV cooperative emergency communications were analyzed.Second, a more general geometry-based stochastic channel model (GBSM) was proposed for multi-UAV cooperative emergency communications.The channel impulse response (CIR) and the cooperative non-station arity of multi-UAV cooperative channels in the space and time domains in multi-UAV cooperative emergency communications were calculated and captured.Finally, the channel characteristics of multi-UAV cooperative emergency communication in urban earthquake and suburban blizzard scenarios were analyzed, which could support the practical implementation of multi-UAV cooperative emergency communications.Meanwhile, the statistical characteristic of the proposed model can fit well with that of ray-tracing-based channel data, verifying the utility of the proposed model.